A technique to establish fistuloclysis for high-output jejunocutaneous fistula through percutaneous enterostomy: A case report. Issue 10 (March 2019) - Niu, Dong-Guang; Yang, Fan; Tian, Wei-Liang; Zhao, Yun-Zhao; Li, Chen; Ding, Lian-An; Fang, Hong-Chun; Huang, Qian
Abstract: Rationale: Currently, fistucolysis helps to establish intestinal nutrition and succus entericus reinfusion in the case of controllable mature high-output enterocutaneous fistula. However, if the tube cannot reach the distal limb of a fistula, fistuloclysis is not achieved. We proposed a strategy to establish succus entericus reinfusion for intractable intestinal fistula through percutaneous enterostomy. Patient concerns: A 43-year-old man was transferred to our facility for postoperative enterocutaneous fistulae, sepsis, malnutrition, and electrolyte and fluid imbalance. The contrast X-ray demonstrated the breakdown of the primary anastomosis, with fistula output ranging from 1500 to 2000 mL/d, despite the administration of medications to reduce gastrointestinal secretions. Diagnoses: The patient was diagnosed with high-output anastomosis fistula by gastrointestinal radiography. Interventions: We used percutaneous enterostomy to establish fistuloclysis. Outcomes: Fistuloclysis was established by percutaneous enterostomy successfully. No complications were found during the past 4-month follow-up after percutaneous enterostomy. He is waiting for reconstruction surgery after 6 months' enteral nutrition (EN). Lessons: Fistuloclysis-assisted EN, if used appropriately, avoids the complications of long-term parenteral nutrition (PN) and may promote faster fistula healing.